PRINCIPAL CHALLENGES IN IMPLEMENTING INSTRUCTIONAL SUPERVISION DURING THE TRANSITION TO THE NEW NORMAL - Rahmat, Baiquni (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2022)
This study explores the challenges that the school principal faced in implementing instructional supervision during the transition period from pandemic era to new normal era. This study uses a qualitative method. This research was conducted at a junior high school in Yogyakarta. The results of this study indicate that during the school transition to the new normal, the principal continues to conduct instructional supervision. The supervision process is carried out using online and face-to-face methods. Principal found various challenges at each stage of supervision. In planning, principal found that there was lack of human resources that are qualified and competent to be a member of instructional supervion team. At the implementation stage, technical problems in the form of poor internet connections available at school made the learning and supervision process became less optimal. Meanwhile, at the follow-up stage, some of programs prepared by the school for teacher competency development were not optimal when that were carried out online.